2021
DOI: 10.12659/ajcr.931639
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Adrenocorticotropic Hormone Deficiency Associated with Severe Hyperkalemia During Pembrolizumab Therapy in a Patient with Ureteral Cancer and an Ileal Conduit: A Case Report and Literature Review

Abstract: Patient: Female, 78-year-old Final Diagnosis: Isolated adrenocorticotropic hormone deficiency Symptoms: Anorexia • general weakness • muscle pain Medication: Hydrocortisone Clinical Procedure: Endocrine test Specialty: Endocrinology and Metabolic Objective: Unusual clinical course Background: Immune checkpoint inhibitors (ICIs) are anticancer medications that enhance the antitumor immune response. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…In our review, the ratio of male patients to female patients was 1.8. The predominance of male patients in ICI-induced IAD was consistent with the review reported by Iglesias ( 10 ) and Hinata ( 11 ). The average age at diagnosis of IAD was also similar, which was mainly affected by the time of onset of the tumor.…”
Section: Discussionsupporting
confidence: 91%
“…In our review, the ratio of male patients to female patients was 1.8. The predominance of male patients in ICI-induced IAD was consistent with the review reported by Iglesias ( 10 ) and Hinata ( 11 ). The average age at diagnosis of IAD was also similar, which was mainly affected by the time of onset of the tumor.…”
Section: Discussionsupporting
confidence: 91%
“…This could lead to delayed diagnosis [2]. However, concurrent hyponatremia could increase the clinical suspicion index of those symptoms as previously reported by others [9,[15][16][17][18][19]. In our case, headaches but not visual disturbances were one of the presenting symptoms.…”
Section: Clinical Presentationsupporting
confidence: 61%
“…Defects of the neurohypophysis are mainly reported in the context of pituitary metastasis [4]. Ascertainment of secondary adrenal failure used different testing strategies, including morning cortisol and ACTH [9,[11][12]15,[17][18][19][20][21][22][23][24][25][26][27], short Synacthen test [12,[16][17][18]21] and corticotropin-releasing hormone (CRH) stimulation test [12,16,24]. In our patient, three pituitary axes were affected: the adrenocorticotropic, thyroid and gonadotrophic axes.…”
Section: Hormonal Disturbancesmentioning
confidence: 99%
“…Although it was not our primary purpose for this study, we identified numerous factors associated with ACU for the population. Some factors associated with the development of irAEs requiring hospitalizations, such as type of ICI agents, 56 platelet count, 57 pre-existing lung, cardiovascular, 56 nutritional, 56 , 58 hyperchloremia, 59 , 60 and infection conditions, 61 are documented in the literature. Variation in red blood cell size and volume is, to our knowledge, not elucidated before and significantly contributes to the accuracy of our XGBT algorithm.…”
Section: Discussionmentioning
confidence: 99%